A coaxial yarn electrode based on hierarchical MoS2 nanosheets/carbon fiber tows for flexible solid-state supercapacitors. Issue 62 (14th June 2016) - Gao, Lili; Li, Xuelian; Li, Xiaodong; Cheng, Jianli; Wang, Bin; Wang, Zhiyu; Li, Changming
Abstract : The carbon fiber tows/hierarchical MoS2 nanosheets (ACFTs/MoS2 ) yarn electrodes synthesized via hydrothermal approach represent hierarchical morphology, coaxial structure, high specific area, excellent electrochemical performance and bending flexibility. Abstract : Coaxial yarn electrodes composed of activated carbon fibers tows and MoS2 nanosheets (ACFTs/MoS2 ) are synthesized by a facile hydrothermal approach. The active material, hierarchical MoS2 nanosheets, delivers a high specific capacitance of 308.5 F g −1 at scan rate of 5 mV s −1 . Solid-state supercapacitors (SCs) in the planar format based on the ACFTs/MoS2 yarn electrode in PVA/H3 PO4 gel electrolyte show an excellent energy density of 3.76 mW h g −1 at constant current density of 0.21 A g −1, a high power density of 474.49 mW g −1 at 3.16 A g −1 and a long cycle life with a capacitance retention as high as 97.38% even after 6000 times of charging–discharging under 2.21 A g −1 . Furthermore, the SCs in a planar format represent superior combination feasibility when combined in parallel or series, approaching the theoretical value. Additionally, twisting SCs made from ACFTs/MoS2 yarn electrodes show good flexibility and electrochemical stability, which maintain 97.6% of their initial capacitance after being bent to different angles. These outstanding performances can be ascribed to the high accessible surface area for the electrolyte, the short path for ion diffusion provided by the MoS2 nanosheets (NSs), as well as the effective transport channels for electrons provided by the carbon fibers. The rough surface and oxygen containing groups on the activated carbon fiber offer robust anchor sites for MoS2 NSs, which not only facilitate electron transport but also provide strong adhesion between MoS2 NSs and carbon fibers.